Optimizing sensory quality and variety: An effective strategy for increasing meal enjoyment and food intake in older nursing home residents. (1st October 2020) - Van Wymelbeke, Virginie; Sulmont-Rossé, Claire; Feyen, Valérie; Issanchou, Sylvie; Manckoundia, Patrick; Maître, Isabelle
Abstract: A decline in appetite and consequently in food intake is often observed with ageing, particularly in older adults living in nursing homes. Several strategies have been tested in nursing homes to counter this phenomenon. However, the approaches have rarely focused on food improvement, and most studies have assessed the impact of flavor enhancement on eating behavior. The present experiment aimed to assess the impact of improving sensory quality versus increasing sensory variety on food intake and meal enjoyment in elderly individuals living in a nursing home. Four conditions were compared: control condition, a Quality+ condition (recipes were improved according to sensory preference of the target population), a Variety+ condition (participants were offered a variety of main dishes and several condiments throughout the meal) and a Quality&Variety+ condition combining the two previous conditions. Eighty-two residents (age range: 71–101 years) participated in eight lunchtime sessions (2 replicates × 4 conditions). Compared to control condition, our results showed that improving the sensory quality of the dishes and/or providing variety led to increased meal enjoyment and food intake (energy intake: +5% for Quality+ ; +7% for Variety+ ). No additional effect was observed when the two factors were combined (+7% for Quality&Variety+ ). These results suggest that meal improvement strategies can be used to increase food intake in order to prevent and treat malnutrition in dependent older adults.